Les territoires au temps du Covid : recherches en sciences humaines et sociales - Lise Bourdeau-Lepage; Guillaume Schmitt; André Torre (Développement Durable et Territoires)
The Covid appeared as a catalyst for emerging and pre-existing phenomena, a revealer of inequalities and a generator of new dynamics within territories. Research in humanities and social sciences has echoed these global and local issues. By focusing on French-language publications between 2020 and 2022, this paper first identifies a trend of the observed facts, before looking at the specific contribution of human and social science approaches dedicated to the Covid period, as well as the evolution of the issues addressed. The final section puts the articles published in this special issue of the DD & T journal devoted to Covid at the territorial scale into perspective in contemporary scientific production.